An analysis of weight perception and physical activity and dietary behaviours among youth in the COMPASS study. (December 2016) - Patte, Karen A.; Laxer, Rachel E.; Qian, Wei; Leatherdale, Scott T.
Abstract: Purpose: Weight misperceptions appear common among youth, potentially influencing their motivation to engage in health-related behaviours; however, the direction of impact remains unclear. The current study examined how weight perception influences physical activity (PA) and diet among youth. Methods: This study used 2-year linked data of 19, 322 grade 9–12 students from Year 2 (Y2 :2013-2014) and 3 (Y3 :2014-2015) of the COMPASS study. Generalized Estimating Equation models tested the effect of Y3 weight perception on the various Y3 PA and dietary behaviour measures, adjusting for Y3 covariates (grade, race/ethnicity, weekly spending money), school cluster, school area median household income, and the Y2 outcome. Models were stratified by gender and body mass index (BMI) classification. Results: Regardless of BMI status, overweight perceptions among boys and girls were associated with lower likelihoods of playing school sports, physical education class enrollment, meeting resistance exercise recommendations, eating breakfast regularly, and less vigorous-intensity PA, and among boys only, lower odds of meeting PA guidelines, compared to their peers who perceived their weight as "about right". In boys with normal-weight BMIs, underweight perceptions predicted less vigorous-intensity PA, and lower odds of physical education class enrollment, and of meeting PA and resistance exercise recommendations, than "about right" perceptions. Among girls, underweight perceptions predicted lower likelihoods of engaging in adequate resistance exercise and playing intramurals, and greater odds of eating fast food on weekends, purchasing snacks, and drinking energy drinks and sugar-sweetened beverages. Girls with overweight/obese BMIs who perceived their weight as such were less likely to consume adequate fruits and vegetables relative to their counterparts with "about right" weight perceptions. Conclusions: Overall, weight perceptions of "about right" appear more favourable for health behaviours among youth across the weight range. Results suggest obesity prevention strategies aiming to increase awareness of weight status may have unintended effects. Highlights: Study on how weight perceptions influence PA and dietary behaviours. Several models tested using linked data from a large cohort of youth. Weight perceptions of "about right" appear most favourable for health behaviours. Both overweight and underweight perceptions were detrimental for PA and diet. Results were consistent regardless of BMI status or gender.